Queens of London : a novel - Webb, Heather, 1976 December 30- (Sourcebooks Landmark, 2024)
"1925. London. When Alice Diamond, AKA "Diamond Annie," is elected the Queen of the Forty Elephants, she's determined to take the all-girl gang to new heights. She's ambitious, tough as nails, and a brilliant mastermind, with a plan to create a dynasty the likes of which no one has ever seen. Alice demands absolute loyalty from her "family"--it's how she's always kept the cops in line. Too bad she's now the target for one of Britain's first female policewomen. Officer Lilian Wyles isn't merely one of the first female detectives at Scotland Yard, she's one of the best detectives on the force. Even so, she'll have to win a big score to prove herself, to break free from the "women's work" she's been assigned. When she hears about the large-scale heist in the works to fund Alice's new dynasty, she realizes she has the chance she's been looking for--and the added bonus of putting Diamond Annie out of business permanently"--